Deep learning : moving toward artificial intelligence with neural networks and machine learning (O'Reilly Media, 2015)
"Push the envelope of data science by exploring emerging topics such as neural networks, deep learnin, speech recognition, and visual intelligence with this video collection, taken from the Hardcore Data Science sessions at Strata + Hadoop World conferences in 2014 and 2015. Learn what neural networks are, how they work, and how they helped achieve the recent record-breaking performance on speech recognition and visual object recognition. Tara presents the latest improvements in deep neural networks (DNNs), including alternative architectures such as Convolutional Neural Networks (CNNs) and Long Short-Term Memory (LSTM) Recurrent Neural Networks (RNNs). Look into computer vision technology, including ongoing projects in large-scale object recognition and visual scene story telling from Stanford Vision Lab. Focus on scalable computational tools for large-scale data analysis, statistical signal processing, and machine learning."--Resource description page.